Women’s Aspiration for Self-Assertion and Self-realization in the Novels of Manju Kapur - Jayant M. Parmar (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2020)
Frequently titled as Advaita philosophy is the devotional literature we find in regional languages of India. As it is more social and cultural, the poets from Bhakti Panth appear more as philosophers and social rather than literary figures. The translation of classics gives sense of belonging especially when a native language gets translated in English. The classics get presented before the world. What Hsuan-tsang did for Sanskrit scriptures, in modern age ShriAurobindo, DilipChitre and A. K. Ramanujan also did in Post Colonial literature which has a heavy flow of translation and Bhakti literature is one of them. This paper discusses about Narsinh Mehta’s philosophical poems which are relevant even in 21st century.